2014
DOI: 10.15623/ijret.2014.0305007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio-Enzyme Stabilization on Unconfined Compressive Strength of Expansive Soil

Abstract: Engineers often face the problem of constructing facilities on or with soils, which do not posses sufficient strength to support the loads imposed upon them either during construction or during the service life of the structure. Vast areas of India consist of Black Cotton Soil which has high clay content, low strength and minimal bearing capacity. The poor engineering performance of such soils has forced Engineers device cost effective and ecofriendly methods for improving the engineering properties of poor so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results obtained from the aforementioned study indicated a decrease in the UCS and the CBR values as the Alkazyme dosage was increased. Puneet and Suneet [15] reported a significant increase in the values of the UCS up to 200% when the soil was treated with Terrazyme, this was in agreement with the findings from other research in the field of Nanomaterial [16].…”
Section: Introduction 1backgroundsupporting
confidence: 91%
“…The results obtained from the aforementioned study indicated a decrease in the UCS and the CBR values as the Alkazyme dosage was increased. Puneet and Suneet [15] reported a significant increase in the values of the UCS up to 200% when the soil was treated with Terrazyme, this was in agreement with the findings from other research in the field of Nanomaterial [16].…”
Section: Introduction 1backgroundsupporting
confidence: 91%
“…Bergmann (2000) concluded through studies that Bio-Enzymes need some clay content to strengthen the soils. It was observed that at least 2% clay is needed for successful stabilization whereas 10 to 15% clay gave very good results 1 . The product formed after the application of TerraZyme is biodegradable in nature and the effect is permanent.…”
Section: Characteristics Of Black Cotton Soil Under Various Enzymesmentioning
confidence: 99%
“…Athira et al [3] mixed the Laterite soil of Kerala with Terrazyme and found an improvement of 139% in CBR value and 281 % in Unconfined compressive strength (UCS) at 28 days of curring. Agrawal [4] mixed 1 ml Terrazyme in 5 kg of Black Cotton soil and found 200 % increases in UCS. Khan et al [5] performed the experiments on clayey soil treated with three different enzymes and found an enhancement in unconfined compressive strength (UCS) and reduction in Swelling and shrinking.…”
Section: Introductionmentioning
confidence: 99%